Патогенез фіброзу печінки та можливості його корекції = Pathogenesis of the hepatic fibrosis and possibilities of its correction = Патогенез фиброза печени и возможности его коррекции - Gorchag, D. M.; Kholodkova, O. L.; Perepeliuk, M. M. (Journal of Education, Health and Sport, 2016)
Gorchag D. M., Kholodkova O. L., Perepeliuk M. M. Патогенез фіброзу печінки та можливості його корекції = Pathogenesis of the hepatic fibrosis and possibilities of its correction = Патогенез фиброза печени и возможности его коррекции Journal of Education, Health and Sport. 2016;6(10):586-600. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.179432 http://ojs.ukw.edu.pl/index.php/johs/article/view/4023 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. УДК 616.36-018.22-092-08 ПАТОГЕНЕЗ ФІБРОЗУ ПЕЧІНКИ ТА МОЖЛИВОСТІ ЙОГО КОРЕКЦІЇ Д. М. Горчаг, О. Л. Холодкова, М. М. Перепелюк Одеський національний медичний університет, м. Одеса Резюме В статті розглянуті основні ланки патогенезу фіброзних змін у печінці за умов негативного впливу та можливі шляхи їх корекції. Обговорені можливості спрямованої індукції зворотного розвитку фіброзу печінки (ФП). Також наведені результати власних досліджень щодо ефективності застосування збагаченої тромбоцитами плазми при ФП. Ключові слова: патогенез; фіброз печінки; регенерація; збагачена тромбоцитами плазма; корекція. PATHOGENESIS OF THE HEPATIC FIBROSIS AND POSSIBILITIES OF ITS CORRECTION D. M. Gorchag, O. L. Kholodkova, M. M. Perepeliuk Odessa National Medical University, Odessa Summary The main links of the hepatic fibrosis pathogenesis under the negative condition are looked out in the article. Possibilities of the directed induction of reverse development of hepatic fibrosis are discussed. The data of own researches of the effectiveness of platelet-rich plasma also shown. Key words: pathogenesis; hepatic fibrosis; regeneration; platelet-rich plasma; correction. ПАТОГЕНЕЗ ФИБРОЗА ПЕЧЕНИ И ВОЗМОЖНОСТИ ЕГО КОРРЕКЦИИ Д. М. Горчаг, О. Л. Холодкова, М. М. Перепелюк Одесский национальный медицинский университет, г. Одесса Резюме В статье рассмотрены основные звенья патогенеза фиброзных изменений в печени в условиях негативного воздействия. Обсуждены возможности направленной индукции обратного развития фиброза печени (ФП). Также приведены результаты собственных исследований об эффективности использования обогащенной тромбоцитами плазмы при ФП. Ключевые слова: патогенез; фиброз печени; регенерация; обогащенная тромбоцитами плазма; коррекция.